Effect of Supply Chain Performance through a Demand and Supply Environment Derived from the ERP System of the Frozen Food Industry in Thailand - tonsakunaree, chanphen; Jaturat, Natnarong; Kuntonbutr, Chanongkorn (Journal of Applied Economics and Management Strategy, 2022)
ABSTRACT The goal of this research is to verify that the efficiency of the supply chain in the frozen food industry of Thailand relates to Enterprise Resources Planning (ERP) systems, which are independent variables, while the information from the demand and supply environment provides mediator variables. Samples were collected from 234 small, medium, and enterprise companies in the frozen food industry of Thailand. The respondents for this study are groups of top executives, middle and operational management and employees utilized within the ERP systems. The data were analyzed by using the Structural Equation Modeling (SEM) method and differed in statistical coefficient, The result of regression weight studies significantly confirmed that the ERP systems had a direct effect on supply chain performance. However, the demand and supply environment also demonstrated indirect relationships with the supply chain performance. In summary, organizations must integrate the model of Enterprise Resource Planning by studying each situation of demand and supply. Furthermore, this model has analyzed the potential of the industry resources for generating sustained competitive advantage for the frozen food Industry in Thailand. Furthermore, the information of the demand and supply environment in the Enterprise Resource Planning (ERP) system confirmed the business value chain in each process and increased the supply chain performance.